Perjalanan Emaus Digital : Mengarungi Ruang Digital dalam Terang Iman kepada Yesus - Sugiyana Sugiyana; Barnabas Bram Suarga (Jurnal Filsafat dan Teologi Katolik, 2024)
This study examines the impact of the use of gadgets and the internet in modern society and how the Catholic Church can provide guidance to its members in addressing the challenges of the digital world. The three research questions addressed are: (1) the impact of gadgets and the internet on behavior and the search for true happiness, (2) the Catholic faith's perspective on the deviant behavior of technology users, and (3) the Church's role in assisting its members in navigating digital challenges. The findings indicate that while the use of gadgets and the internet facilitates communication and entertainment, it can also lead to social disconnection and an unfulfilled search for happiness. The Church, through Catholic teaching, provides moral guidance to mitigate these negative impacts by emphasizing the importance of harmonizing technological advancements with fundamental human values. In the digital realm, the Church plays a strategic role in fostering solidarity and offering a space for authentic spiritual experiences, particularly for the younger generation that is highly dependent on technology, which can be referred to as the "New Emmaus." This study concludes that the Church can reach more believers by creatively utilizing digital platforms and guiding them toward a deeper search for faith amidst the challenges of the digital culture.